How to promote the class engagement of graduate students in seminar teaching: An empirical research - Liu Yexin; Gao Pengbin; Wu Weiwei (SHS Web of Conferences, 2022)
Student engagement is of critical importance because it can help students gain more knowledge from the course. This paper investigates how to improve student engagement of graduate students in seminar teaching, and the results show that student self-efficacy, classmate support, and teacher support have significant positive effects on student engagement. These findings highlight the value of self-efficacy, classmate support, and teacher support. Therefore, college should take measures to promote self-efficacy, classmate support, and teacher support.